Preventive effects of Topiramate on methylphenidate induced behavioral disorders - Nobakht-Haghighi, Navid; Motaghinejad, Majid; Motevalian, Manijeh; Safari, Sepideh (Ms-Editions, 2019)
Neuronal cell damage is often caused by prolonged misuse of Methylphenidate (MPH). Topiramate (TPM) carries neuroprotective properties but its assumed mechanism remains unclear. The present study evaluates in vivo role of various doses of TPM and its mechanism against MPH-induced motor activity and related behavior disorder. Thus, we used domoic acid (DOM), bicuculline (BIC), Ketamine (KET), Yohimibine (YOH) and Haloperidole (HAL) as AMPA/kainite, GABAA, NMDA, alpha 2 adrenergic and D2 of dopamine receptor antagonists respectively. Open Field Test (OFT), Elevated Plus Maze (EPM) and Forced Swim Test (FST) were used to study motor activity, anxiety and depression level. TPM (100 and 120 mg/kg) reduced MPH-induced rise and inhibited MPH-induced promotion in motor activity disturbance, anxiety and depression. Pretreatment of animals with KET, HAL, YOH and BIC inhibited TPM-improves anxiety and depression through the interacting with Dopaminergic, GABAA, NMDA and alpha 2-adrenergic receptors.
Keywords: Methylphenidate; Topiramate; Neurobehavioral changes; Glutamatergic; GABAergic; Adrenergic; Dopaminergic